Effect of Internal Marketing on Internal Supply Chain Management through Mediation of Employees’ Affective Commitment - Bin Thabet, Omer Ahmed Salmeen; Lee, Hoyoung; Khalid, Nadeem (International Journal of Supply Chain Management, 2019)
This study examined the relationship of internal marketing and employees’ affective commitment with internal supply chain integration. Furthermore, this study also uncovered the mediation mechanism by proposing employees’ affective commitment as mediator between internal marketing and internal supply chain integration for services firms. Data of 245 usable responses was collected from five major banks of Thailand through self-administered questionnaire by utilizing convenience sampling. Structural equations modeling was carried out in Smart-PLS 3 in order to test the proposed hypotheses. Results depicted that internal marketing is a significant predictor of internal supply chain integration and this relationship becomes stronger with the intervention of employees’ affective commitment. This study sheds a light on the importance of employees for service organizations and provide a way forward to managers for policy making about their employees in order to develop profitable and competitive assets for the organization.